ANALISIS KINERJA KEUANGAN PT. WIJAYA KARYA (PERSERO) TBK PERIODE 2012 -2016 - Yulia Yulia (Universitas Mercu Buana, 2018)
ABSTRACT Progress of a company can be seen from the financial aspect. The most common form of enterprise information is a set of financial statements made under the guidelines. Financial statements made under applicable guidelines, rounds of decisions made in the past and present. Developing the open needs to be based on the tools and capabilities that can drive the company toward efficiency and competitiveness. The purpose of this study is to determine the financial performance of PT. Wijaya Karya (Persero) Tbk period 2012 - 2016. Based on the assessment in accordance with the decision of the Minister of State-Owned Enterprises Number: KEP-100/ MBU/2002. This research is a type of research which is secondary data. The required documents are the annual report financial statements of PT. Wijaya Karya (Persero) Tbk period 2012 - 2016. Data analysis techniques using evaluation techniques based on the decree of the Minister of State-Owned Enterprises Number: KEP-100 / MBU / 2002. Based on the results of research shows the financial performance of PT. Wijaya Karya (Persero) Tbk three years consecutive year 2012-2014 pred predicate Health Category AA with of 2012 total score 81,79, 2013 total score 82,5, and year 2014 total score 86,43. Further reviewed, the 2015 and 2016 total score decreased in 2015 total score of 73.21 and 2016 total score of 72.86, with predicate Health Category A. Keyword : Financial Performance, Trend Analysis, The Decree of the Minister of State-Owned Enterprises Number: KEP-100 / MBU / 2002